2012
DOI: 10.1371/journal.pone.0041284
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi IV Causing Outbreaks of Acute Chagas Disease and Infections by Different Haplotypes in the Western Brazilian Amazonia

Abstract: BackgroundChagas disease is an emergent tropical disease in the Brazilian Amazon Region, with an increasing number of cases in recent decades. In this region, the sylvatic cycle of Trypanosoma cruzi transmission, which constitutes a reservoir of parasites that might be associated with specific molecular, epidemiological and clinical traits, has been little explored. The objective of this work is to genetically characterize stocks of T. cruzi from human cases, triatomines and reservoir mammals in the State of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 68 publications
1
61
0
3
Order By: Relevance
“…Trypanosoma cruzi isolates were typed using three different parasite genomic sequences as reported (39) , with the 24Sα ribosomal (rRNA) gene D7 domain (40) , mitochondrial cytochrome oxidase subunit 2 gene (COII) (41) , and the spliced leader genes intergenic region (42) as markers for six discrete typing units (DTUs) (43) , using T. cruzi reference strains (15) (44) (45) and clones (46) (47) as DTU controls.…”
Section: Trypanosoma Cruzi Isolates For Genotypingmentioning
confidence: 99%
“…Trypanosoma cruzi isolates were typed using three different parasite genomic sequences as reported (39) , with the 24Sα ribosomal (rRNA) gene D7 domain (40) , mitochondrial cytochrome oxidase subunit 2 gene (COII) (41) , and the spliced leader genes intergenic region (42) as markers for six discrete typing units (DTUs) (43) , using T. cruzi reference strains (15) (44) (45) and clones (46) (47) as DTU controls.…”
Section: Trypanosoma Cruzi Isolates For Genotypingmentioning
confidence: 99%
“…Studies in Amazonas have demonstrated the presence of DTUs TcI, TcIII and TcIV in the parasite sylvatic transmission cycle (33) (34) (35) (38) . TcIV predominates among orally transmitted acute human cases (34) , and TcI predominates among the isolated and chronic cases (35) (38) , suggesting their association with different transmission profiles. The T. cruzi isolates showed variable behavior in experimental infections in mice, promoting low parasitemia, virulence and pathogenicity, which is compatible with the low parasitemia and morbidity profi le of CD in humans and with the poor performance of diagnostic methods in the region (43) .…”
Section: Chagas Disease In the State Of Amazonasmentioning
confidence: 99%
“…A total of 18 T. cruzi strains were studied; 14 were isolated from patients during the acute phase of infection, vectors and wild reservoirs from the State of Amazonas and were classified as TcI (6) and TcIV (8), 13 and four strains were isolated from chronically infected patients residing in the State of Paraná and were genotyped as TcII 20 (Table 1). Parasites were maintained in culture in liver infusion tryptose (LIT) medium by successive subculturing with alternating mouse-LIT-mouse passages and in blood passages in mice at the Chagas Disease Laboratory (Laborató rio de Doença de Chagas), Maringá State University (Universidade Estadual de Maringá ; UEM).…”
Section: Methodsmentioning
confidence: 99%
“…To date, knowledge about these T. cruzi DTUs in the Amazon region is scarce, and pioneer studies from our group present a detailed understanding of the genetic, biological, and histopathological characteristics of parasites belonging to TcI and IV DTUs. [13][14][15][16][17] The goal of etiologic treatment of CD is the parasite elimination from the infected individual, thereby inhibiting clinical evolution and breaking the disease transmission chain. 18 Histologically, the acute phase of trypanosomiasis is a systemic infection, and intracellular forms of the parasite can be found in all organs.…”
Section: Introductionmentioning
confidence: 99%